Pediatric Altered Mental Status - Margaret Wolff; L Skaugset; Jennifer Jachowski; Alex Rogers (Association of American Medical Colleges, 2014)
Abstract Introduction The purpose of this module is to teach health care professionals about the presentation, evaluation, and initial management of altered mental status in children. Altered mental status in a child is a potentially life-threatening condition with a broad differential including vascular, toxin-mediated, infectious, metabolic, and traumatic causes. Therefore, medical providers who care for children should be well versed in the identification and initial evaluation and management of these patients to ensure they can act quickly when necessary. Methods This interactive learning module is designed to be used in a 1-hour classroom session. Included in the resource are an instructor's guide, PowerPoint presentation with presenter notes, pretest, small-group activity, and other associated materials. This module has been used with pediatric residents, emergency medicine residents, and pediatric emergency medicine fellows. Results Approximately 90 learners have completed this module during four separate sessions and the module has been modified based on their feedback. The mean score on the pretest was 60% with only 25% of learners being able to describe an initial approach to a child with altered mental status. In contrast, 94% of learners successfully created an algorithm for the initial management of a child with altered mental status at the conclusion of the module. Discussion Altered mental status in a child is a potentially life-threatening condition with a broad differential including vascular, toxin-mediated, infectious, metabolic, and traumatic causes. We believe this is an effective module that will be useful for anyone involved in the acute care of children.